Sintesa dan Karakterisasi Biofuel dari Limbah Laboratorium Teaching Factory Politeknik Negeri Lhokseumawe dengan Proses Catalytic Cracking - Muammar Khadafi; Ratni Dewi; Adriana Adriana; Ratna Sari; Lukman Hakim (Jurnal Serambi Engineering, 2021)
Spent earth is a waste resulting from the bleaching process which contains gums and a large amount of oil so that it still has the potential to be reprocessed into biofuel. This study aims to utilize the oil from spent earth as a raw material in the synthesis of biofuels through the catalytic cracking process. In the catalytic cracking process, zeolite and kaolin catalysts are used in the ratio (0:100); (30:70); (50:50); (70:30) and (100:0) and temperature variations of 150oC, 175oC and 200oC for 3 hours. Based on the research results, the best biofuel was obtained at a catalyst ratio of zeolite: kaolin (70:30) and a temperature of 200oC with a yield of 76.13%. The results of the biofuel characterization obtained a water content of 0.0301%, octane number 90.5 RON and a density 751 kg/m3. Analysis of biofuel composition was measured using GC-MS and it was found that the biofuel contained 4.60% C11H24, 8.99% C12H26, 22.49% C16H34, 9.54% C18H34O2 and 54.38% C19H36O3. Based on the physical and chemical properties of the biofuel as a result of cracking with zeolite and kaolin catalysts, it is in accordance with SNI for gasoline qualification.